Manajemen Supervisi Kepala Sekolah Pada Kinerja Guru - Syarifah Syarifah (Fakultas Tarbiyah dan Keguruan, 2022)
I carried principal supervision management on teacher performance out to motivate teachers in teaching. This study describes the supervisory management of school principals on teacher performance. The research method uses a Literature Review design. I do this in order to critically evaluate information, ideas, or findings in the academic literature and plan theoretical and methodological contributions to themes related to supervisory management, principals and teacher performance. The results show that supervision is a form of professional help offered to teachers to improve learning performance. This structure will create contact between principals and instructors who will accept the abilities and shortcomings that are assessed in supervised activities. Therefore, the role of the principal is very important in motivating teachers to develop their professionalism by maximizing supervision activities through effective management.